Synergism of antitumor action of dioxadet and cisplatin in model of ascitic ovarian tumor - V. G. Bespalov; A. A. Zhabin; A. N. Stukov; O. A. Beliaeva; If. G. Murazov; A. L. Semenov; S. A. Kon’kov; I. M. Krylova (Сибирский онкологический журнал, 2016)
Comparative antitumor activity of cytostatics dioxadet, cisplatin and their combination was studied in model of ascitic ovarian tumor in 38 female Wistar rats. Ascitic ovarian tumor was transplanted intraperitoneally at amount of 5 × 106 tumor cells per rat. Dioxadet andcisplatin were administered intraperitoneally at their single maximal tolerable doses 48 hours after the tumor transplantation: 1,5 and 4,0 mg/ kg b.w., respectively. Drug combination of dioxadet and cisplatin administered by the same way but at one half of maximal tolerable doses. Antitumor effects of the drugs were estimated by increasing life span of the animals. In control group without treatment the average life span was 16 ± 6,3 days. Dioxadet and cisplatin showed comparable antitumor activity increasing the average life span by 63,1 % and 48,1 %, correspondingly. Drugs combination showed synergistic effect increasing average life span by 107,5 % (p<0,05). Moreover, combinationof dioxadet and cisplatin are characterized by less toxicity compared with cisplatin applied in maximal tolerable dose.